Catecholaminergic neuronal network dysfunction in the frontal lobe of a genetic mouse model of schizophrenia. Issue 2 (3rd September 2015) - Iritani, Shuji; Sekiguchi, Hirotaka; Habuchi, Chikako; Torii, Youta; Kuroda, Keisuke; Kaibuchi, Kozo; Ozaki, Norio
Abstract : Background: The precise aetiology of schizophrenia remains unclear. The neurodevelopmental hypothesis of schizophrenia has been proposed based on the accumulation of genomic or neuroimaging studies. Objective: In this study, we examined the catecholaminergic neuronal networks in the frontal cortices of disrupted-in-schizophrenia 1 (DISC1) knockout (KO) mice, which are considered to be a useful model of schizophrenia. Methods: Six DISC1 homozygous KO mice and six age-matched littermates were used. The animals' brains were cut into 20-μm-thick slices, which were then immunohistochemically stained using an anti-tyrosine hydroxylase (TH) monoclonal antibody. Results: The TH-immunopositive fibres detected in the orbitofrontal cortices of the DISC1 KO mice were significantly shorter than those seen in the wild-type mice. Conclusion: These neuropathological findings indicate that the hypofrontal symptoms of schizophrenia are associated with higher mental function deficiencies or cognitive dysfunction such as a loss of working memory.